Community pharmacists’ views towards implementing a patient self-administered screening tool designed to identify risk of medication-related problems - Salahudeen, Mohammed S.; Saadeldean, Ahmed Samy; Peterson, Gregory M.; Tesfaye, Behailu Terefe; Curtain, Colin M. (Frontiers in Pharmacology, 2025)
ObjectiveThere is limited information regarding community pharmacists’ perspectives on implementing a self-administered screening tool for identifying patients at risk of medication-related problems. This study assessed Australian pharmacists’ views on introducing such a tool within the community pharmacy setting.MethodsAn online cross-sectional survey was conducted among Australian community pharmacists from March to May 2023. The survey collected relevant demographic data and responses on perceived barriers and facilitators to implementing the screening tool. Reliability statistics were computed for the responses on barriers and facilitators, and chi-square or Fisher’s Exact tests were performed to assess their association with demographic variables.ResultsTwo hundred thirty-one community pharmacists across Australia were surveyed. Most (78%) reported that medication-related problems are common and expressed support for a patient self-administered screening tool to identify patients at high risk of medication-related problems (88%). Over two-thirds (69%) were willing to allocate time for reviewing patient medications if flagged for medication-related problems. The most frequently anticipated barriers to implementing screening tools were time constraints for pharmacists (63%), staff shortage and limited patient interest (each accounting for 57%). In contrast, effective communication with patients (69%) and patients’ appreciation of pharmacists’ expertise and efforts (67%) were predominantly stated facilitators.ConclusionMost community pharmacists were supportive of implementing a patient self-administered screening tool to identify patients at risk of medication-related problems. The study’s findings provide valuable insights for developing medication-related problems screening tools tailored to the Australian community pharmacy setting.